Effect of chronic ammonia nitrogen stress on the SOD activity and interferon-induced transmembrane protein 1 expression in the clam Cyclina sinensis - Ge, Hongxing; Ni, Qian; Liu, Jialing; Dong, Zhiguo; Chen, Shibo (Frontiers in Marine Science, 2022)
Ammonia nitrogen plays a crucial part in oxidative stress in aquatic animals. To elucidate the effect of ammonia nitrogen stress on the SOD activity and interferon-induced transmembrane protein 1 (IFITM1) expression in clam Cyclina sinensis, the clam was exposed to ammonia nitrogen (8.07 mg/L) for 768 h (32 d) and then challenged with Vibrio parahaemolyticus. The result showed that the SOD activity in the hepatopancreas of C. sinensis exposed to ammonia nitrogen first increased and then decreased with time, and the SOD activity resumed to the control group's level normally at 768h. Following infection with V. parahaemolyticus, the SOD activity in the hepatopancreas fluctuated over time. The SOD activity in the clam infected with V. parahaemolyticus in 144h can’t resume to the control group's level normally. The full-length cDNA of CsIFITM1 was 2434 bases in length, including a 2301-bp open reading frame (ORF) encoding 714 amino acids, with a putative molecular weight of 83.86 kDa. The CsIFITM1 protein contained an RNA helicase domain (DEXHc_RLR, DR) and a Helicase_C domain (HC). The transcriptional levels of CsIFITM1 were up-regulated by ammonia nitrogen, and it was significantly higher from 6h to 768h than the control (0h) (P<0.05). Following infection with V. parahaemolyticus, the CsIFITM1 transcript levels in hepatopancreas were up-regulated, and it was significantly higher from 6h to 144h in contrast to the control (0h) (P<0.05). The present data provide the ﬁrst evidence that the SOD activity and CsIFITM1 transcript levels can reflect the effect of ammonia on the clam C. sinensis.